Food safety governance: Standard operating procedure on controlling of nitrite level, handling and processing of edible bird's nest - Ramli, Noriah; Azmi, Saiful Mohammad Nizam (INSI Publications, 2012)
Malaysia is one of the largest bird’s nest exporters particularly to China and Hong Kong market. However, Malaysia multimillion ringgits bird’s nest industry has been hit hard by China’s ban and a series of scandals, with a drop in sales and prices. In light of the emerging food safety issues that surrounds the Malaysian Edible Bird’s Nest (EBN) industry, which have somewhat affect the economic gain of the EBN exporters in Malaysia, the Ministry of Health Malaysia, the Ministry of Agriculture and Agro-based and Industry Malaysia under its Department of Veterinary Services (DVS) and Department of Standards Malaysia had since 2003 issued a set of guidelines for a more systematic management of the local swift’s nest industry. Besides, these guidelines are needed to ensure that the local swiftlet’s industry does not create any health problem to the population.